The cardiac electrophysiology-inspired patches for repairing myocardial infarction: A review - Songtao Zhang; Ziyi Shao; Yihong Wu; Yongyi Song; Yaxi He; Zongyi Liu; Xiaodong Fu; Leyu Wang (Smart Materials in Medicine)
Myocardial infarction has been a serious threat to human health due to its high morbidity and mortality all over the world. The major problem is the loss of limited regenerative cardiomyocytes and occurrence of inflammatory response, leading to the formation of non-contractile and non-conducting fibrotic scar tissue. Thus, it disrupts the mechano-electric coupling system of the heart, negatively influencing the heart function. Recently, the conductive cardiac patches with advantage of reconstructing electrical propagation have been extensively applied for cardiac repair. This review introduces a detailed overview of the recent progress in cardiac electrophysiology-inspired patches for cardiac repair from three parts of the construction and functionality of mechano-electric coupling cardiac patches, the construction and functionality of microstructure of the cardiac patches, the realtime detection based on mechano-electric transformation. Finally, the achievements and future perspective of conductive cardiac patches is discussed from the aspects of biosafety, further exploration of factors affecting mechano-electric coupling in cardiac patches and regulation of detection. It is hopeful to help researchers understand the functional components and development of conductive cardiac patches for cardiac repair, as well as to inspire them to synthesize novel cardiac patches for promoting clinical translation.